Draft Annual Plan (1970-71) Part-II Union Territory of Delhi - Planning Commission (Planning Commission, 1970)
Cooperation & Pawchayats Cooperation Panehayats Irrigation & Power Mood Control Power Industries Roads & Road Transport Roads Road Transport General Education & Cultural Pb0Gram1E Technical Education Health Water Supply & Drainage Housing & Urban Development Important Projects Costing Rs.L Crore & Above Check List In Respect Of Principal Projects Costing Rs.L Crore & Above. Physical Programmes Centrally Sponsored Sche14Es
Planning Department Delhi Administration